The cut-off value for HOMA-IR discriminating the insulin resistance based on the SHBG level in women with polycystic ovary syndrome - Biernacka-Bartnik, Aleksandra; Kocełak, Piotr; Owczarek, Aleksander Jerzy; Choręza, Piotr Stanisław; Markuszewski, Leszek; Madej, Paweł; Puzianowska-Kuźnicka, Monika; Chudek, Jerzy; Olszanecka-Glinianowicz, Magdalena (Frontiers in Medicine, 2023)
Introduction The study aimed to estimate the cut-off value for homeostatic model assessment for insulin resistance (HOMA-IR) discriminating the insulin resistance based on the sex hormones binding globulin (SHBG) level in women with polycystic ovary syndrome (PCOS). Materials and methods Data from medical records of 854 Caucasian women diagnosed with PCOS were analyzed. Anthropometric data, fasting plasma glucose, insulin and SHBG levels were measured. HOMA-IR was calculated with a standard formula. The cut-off value was calculated using receiver-operating characteristics. Results Circulating SHBG levels below the normal range (26.1 nmol/L) were found in 25.4% of study participants. This subgroup had a significantly higher BMI, fasting glucose and insulin concentrations and HOMA-IR values. Empirical optimal cut-off values for HOMA-IR corresponding to low SHBG levels was ≥2.1 [area under the curve (AUC) 0.73, accuracy 0.65, sensitivity 72.3%, specificity 63.1%, positive predictive value (PPV) 40.0%, negative predictive value (NPV) 87.0%]. Conclusions Our study suggests that the cut-off point for HOMA-IR discriminating the insulin resistance based on the SHBG level, in young Caucasian women with polycystic ovary syndrome is 2.1, and is consistent with the cut-off value adopted by the European Group for the Study of Insulin Resistance (above 2.0).